The Organizations and based systems thinking and hermeneutics phenomenology (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This paper demonstrates the use of the current epistemological and hermeneutic phenomenology through systems theory specifically in the study of organizations. The development of these approaches begin with background exposure and conceptualization of phenomenology and later mentioned the hermeneutic turn that it did. And finally to address the application of the above mentioned epistemological currents developed in management science in the field of the organizations analyzed by hermeneutic phenomenological method systems theory.
Keywords: phenomenology; hermeneutics; organizations; systems theory